1997
DOI: 10.1002/anie.199718661
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Molecular Ratchets

Abstract: COMMUNICATIONS tural feature of these (TMPDO),TCNE arrays is rectangular four-site 0 -C binding at the TCNE olefinic carbon atoms, which appear to interact through their K* lobes. The topological requirement for DA complexation at the N-oxide center is more flexible, allowing the formation of both ladder and web (crosslinked ladder) DA arrays in the (TMPDO),TCNE crystals as the N-0-C angle flexes. TMPDO (2.58 g, 69%, m.p. 498 K (493 K 1221) was prepared by treatment of 2,3,5,6-tetramethylpyrazine (2.95 g, Ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(86 citation statements)
references
References 32 publications
3
80
0
Order By: Relevance
“…22 Their designs culminated in a system that employed chemical reactions to bias a 120 degree rotation of a triptycene residue in one direction, 23 but attempts to extend this approach to repetitive 360 degree directional rotation proved unsuccessful. 24 Light-driven rotary molecular motors based on overcrowded alkenes 12,13 and imines 14,16 have been developed by the groups of Feringa and Lehn, while our group 25,26 and others [27][28][29] have made molecules in which the components can be rotated directionally step-wise by repetitively carrying out several chemical reactions in sequence.…”
mentioning
confidence: 99%
“…22 Their designs culminated in a system that employed chemical reactions to bias a 120 degree rotation of a triptycene residue in one direction, 23 but attempts to extend this approach to repetitive 360 degree directional rotation proved unsuccessful. 24 Light-driven rotary molecular motors based on overcrowded alkenes 12,13 and imines 14,16 have been developed by the groups of Feringa and Lehn, while our group 25,26 and others [27][28][29] have made molecules in which the components can be rotated directionally step-wise by repetitively carrying out several chemical reactions in sequence.…”
mentioning
confidence: 99%
“…Among the fascinating structures designed to induce mechanical motions are shuttles, muscles, ratches, pseudorotaxanes, and switches (5)(6)(7)(8)(9)(10)(11)(12). Recently, the first examples of unidirectional rotary motors were reported (13,14), and it was shown that the rate of the rotary motion in the light-driven motors could be tuned by structural modification (15).…”
mentioning
confidence: 99%
“…Molecular rotors driven unidirectionally by light (8), or bidirectionally by heat (9)(10)(11)(12) or chemically (13,14) have been synthesized. Alternating electric field has been used to affect intramolecular motion (15), and intense laser field of rapidly rotating linear polarization has been used to drive the rotation of a chlorine molecule (16).…”
mentioning
confidence: 99%